Regional policy effect on photovoltaic (PV) technology innovation: Findings from 260 cities in China. (March 2022) - Che, Xiao-Jing; Zhou, P.; Chai, Kah-Hin
Abstract: Photovoltaic (PV) technology innovation is one of the important ways to achieve energy transition in China. To overcome market failures and institutional barriers, policy support is necessary for PV technology innovation. As regions are the main actors in the technology innovation process, more attention should be paid to regions when designing a PV policy. Therefore, this study assesses the effects of regional policies on PV technology innovation using a large panel data on 260 cities in China from 2007 to 2018. The empirical results show that city-level PV incentive policy instruments have a significant effect on PV technology innovation, but applying more PV policy instruments simultaneously is not always better. Moreover, city-level demand-, supply-, and environment-side policies play an important role in urban PV technology innovation, and a high balance among the three types of PV policy can make their innovation effect better. Finally, this study also finds that the effects of different city-level PV policy instruments on PV technology innovation are heterogeneous. Not only that, the effectiveness of these city-level PV policy instruments on PV technology innovation is also affected by urban heterogeneities. Highlights: Assess the effect of regional PV policies on technology innovation at city level. Effects of various PV policy instruments on technology innovation are heterogeneous. Balance between demand-, environment-, and supply-side PV policy instruments is needed. The regional heterogeneity on the impact of PV policy instruments has been identified.